Key Success Factors in Social Enterprise Proposals: Insights from Social Entrepreneurship Projects in Education - Romi Kurniadi; Suratno Suratno (AL-ISHLAH: Jurnal Pendidikan, 2024)
Social entrepreneurship education is crucial for cultivating entrepreneurial mindsets and addressing societal challenges, particularly in developing regions. This study explores the themes and priorities emerging from student-generated social enterprise proposals within a project-based learning program. A qualitative case study approach, grounded in the interpretivism paradigm, was employed to analyze 11 social enterprise proposals developed by 110 students. Reflexive thematic analysis was utilized to identify key patterns and themes in the proposals. The analysis revealed that students emphasized community benefits, such as job creation and income generation, and innovative approaches, including technology integration and product diversification. However, the concept of social risk-taking, a fundamental aspect of entrepreneurial intention, was notably underrepresented in the proposals. The underrepresentation of social risk-taking underscores a gap in current educational frameworks. Incorporating experiential learning opportunities and risk management strategies could better prepare students for the complexities of real-world social entrepreneurship. These findings align with established principles of social entrepreneurship while also highlighting divergences that inform future curriculum development. This study contributes to the literature on social entrepreneurship education by illustrating how student perceptions align with and diverge from the core principles of social entrepreneurship. The findings provide actionable insights for designing curricula that more effectively equip students with the skills and mindset necessary for successful social entrepreneurial ventures.